Analysis Characteristics Hybrid Coolant Nanoparticles As a Cooling Media for Genset Generator - Rantawi, Azhar Basyir; Saputra, Hendra; Siregar, Ahdiat Leksi; Rahardja, Istianto Budhi; Susanto, Edy; Ramadhan, Anwar Ilmar (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
Industry nanotechnology- based is a very significant new modern era, where throughout field develop and use it. In the world of technology as primary needs at the moment This for society, has Lots use results its products. Cooling system as balancers in the industrial world including generators require gensets research and development For cool diesel generator engine . Hybrid coolant has composition 30% material natural and 70% distilled water. The addition nanoparticles to in hybrid coolant of 1% (TiO2-SiO2-Al2O3 ). The test was carried out is temperature point education, pH value, density. Analysis results The characteristics of hybrid coolant are point boiling 99°C, pH value between 5.79-6.06, as well mark density of 1,012-1,024.